2020
DOI: 10.1002/edm2.200
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control, associated factors, acute complications of Type 1 Diabetes Mellitus in children, adolescents and young adults in Tanzania

Abstract: Objective To determine the factors associated with poor glycemic control in children (1‐10 years), adolescents (11‐18 years) and young adults (19‐40 years) with Type 1 Diabetes Mellitus (T1DM) in Kilimanjaro Christian Medical Center (KCMC) in Moshi, Mount Meru Regional Referral Hospital (MMRRH) and Meru District Hospital (MDH) in Arusha, Tanzania. Methods Cross sectional study of 150 participants conducted from January to June 2019, data was collected by structured questionnaire and analyzed using SPSS version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
5
10
1
Order By: Relevance
“…This study indicated that duration of DM was not significantly associated with poor glycemic control. This is similar with studies conducted in Tanzania, and India, which found that the duration of DM was not a significant predictor of poor glycemic control 6 , 11 . But, studies conducted in Amhara region, Shanan Gibe, Egypt, Jimma, and Nekemte showed that duration of DM was significantly associated with poor glycemic control 2 , 8 , 17 , 23 , 31 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study indicated that duration of DM was not significantly associated with poor glycemic control. This is similar with studies conducted in Tanzania, and India, which found that the duration of DM was not a significant predictor of poor glycemic control 6 , 11 . But, studies conducted in Amhara region, Shanan Gibe, Egypt, Jimma, and Nekemte showed that duration of DM was significantly associated with poor glycemic control 2 , 8 , 17 , 23 , 31 .…”
Section: Discussionsupporting
confidence: 90%
“…The risk of poor glycemic control was reduced by increasing treatment dose by one IU until it reached recommended dose. However, the study conducted in Tanzania indicated that dose of treatment is not a significant predictor of poor glycemic control 6 . The discrepancy might be due to the difference in study participant, sample size and setting.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Both in developed and developing nations, the prognosis for children with T1DM is poor [9]. As a result, OGC oscillated from 2.6-9.8% in Tanzania [12,13], 24% in Cameron [9], 24% in Sudan [14] 28% in Egypt [15]; 20.9% in Jordan [16] 39.1% in Saudi Arabia [17] and 33,36% in California [18] and Bulgaria [19] respectively. Many are not detected and those diagnosed have dramatically reduced their life expectancy by 1 year, [20].…”
Section: Introductionmentioning
confidence: 99%